Viabilidade e expressão de transcritos de virulência em Campylobacter jejuni experimentalmente inoculados em queijos minas frescal - Monteiro, Guilherme Paz (2013)
This study evaluated the viability and capability of transcription of genes ciaB, dnaJ, p19, sodB by two strains of Campylobacter jejuni (NCTC 11351 and IAL 2383) retrieved from Minas Frescal cheeses, made with pasteurized milk experimentally inoculated with the micro-organism. The cheeses were stored at 4 °C for 10 days and periodi cally evaluated for the presence/quantify of coliform group, Staphylococcus coagulase positive, Campylobacter jejuni, besides acidity, pH, umidity and sodium chloride. The Campylobacter isolates recovered from cheeses were evaluated by RT-PCR technique to check if there was a change in their transcriptomes. Storage at 4º C reduced the counts of C. jejuni from the first to the fourth day and led to undetectable levels after the seventh day. The decrease of umidity and pH and the increasing of acidity in Minas Frescal was correlated with the decrease in viability of C. jejuni. There was a reduction in the production of transcripts of the four genes tested, more pronounced on the fourth day of storage, when p19 and sodB transcripts have not been found anymore. The consumption of Minas Frescal cheese contaminated with Campylobacter can be threatening to infect humans when consumed up to four days after its manufacture.